DARI AKSI HINGGA PESTA DEMOKRASI: DINAMIKA PARTAI RAKYAT DEMOKRATIK MENUJU PEMILU (1996-1999) - Cahyo Susilo (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2019)
This research illustrated the historical event in Indonesia, especially in 1990s period. The study examined the development of People Democratic Party as one of the political parties in the New Order regime. This research-based on the author’s interest in the pro-democracy movement’s widespread in Indonesia, evidenced by the resistance movement of peoples, in this case, is the People Democratic Party. The study aimed to identify programs and strategies of the People Democratic Party to build a pro-democracy movement in the 1996-1999 period. The author used the historical method. People Democratic Party was one of the political party which develop at that time and had a political movement to subvert a New Order regime. People Democratic Party often referred to as a radical political party, because of the political program that confronted the New Order regime namely to eliminate the Indonesian National Armed ForcesDual function, to eliminate a five-pack of Political Act and Timor-Timur referendum. The impact, People Democratic Party regarded as a forbidden party and accused as the actor behind July 27th 1996 tragedy. After the tragedy, the People Democratic Party arose with people’s committees. The four elements of People Democratic Party namely (1) the urban poor, (2) workers, (3) youth people, (4) PDI-Megawati supporters. After 1998 Reformation, People Democratic Party declared as a legal party and has participated as a contestant of 1999 electoral. People Democratic Party argued that the Electoral system is a moment for campaigning political programs. Several thingsin the campaign was about amnesty for political prisoners, completion of Civil Rights violation cases, and people’s political rights.